ENT300 Enterpreneurship Proposal Rasa D'borneo Bistro Pte. Ltd / Mohd Haziq Karem... [et.al] - Karem, Mohd Haziq; Hamiddon, Rozainah; Selimah, Boniface; Rapa'ee, Nurmashitah; Tupi, Laura Peritha (2010)
Four of shareholders have entitled to the management of the company according to their skills, ability and also their experience. The company is lead by the General Manager. This follows by Administration Manager, Marketing Manager, Operation Manager and Financial Manager. Besides that we also have general workers. The wedges are paid monthly and incentive such as EPF, SOCSO, annual leaves; medical expenses are given to the workers. Marketing strategies is very essential in making profit in the company. Our targets are customers in Kuching and Satok. Even though there are some fights from the other companies, we are sure with good marketing strategies we can survive the market and gain profit, and despite of the risk. Operation of our product is producing and selling. We ensure that everything is well kept. We also ensure that the surrounding area is comfortable and nice for all the workers and also the customers which come to our bistro. The target of our operation is to produce a high quality and delicious food and perfect service for the customers and to full fill the demand. Meanwhile in financial, we decide to make a loan of RM26, 702.00 from the Agro Bank to motivate our business plan. Our shareholders contribute RM15, 000.00 each except General Manager which contributes RM 18,986.00 with an effective accuracy and honesty in financial management; we hope that the company can stand strong thru the year coming.